DOP80 Integrated tissue transcriptomic and serum proteomic interrogation reveals biomarkers for endoscopic improvement and histologic remission after JAK3/TEC inhibition in Ulcerative Colitis (UC) (Phase 2b Vibrato study). (21st January 2022) - Hassan-Zahraee PhD, M; Ye, Z; Xi, L; Banerjee, A; He, W; Dushin, E; Lee, J; Altintas, E; Romatowski, J; Leszczyszyn, J; Danese, S; Sandborn, W J; et al.
Abstract: Background: Ritlecitinib (PF-06651600) is an oral Janus kinase 3/TEC inhibitor, demonstrated to be safe, well-tolerated and efficacious in moderate to severe active ulcerative colitis. The aim of this pre-specified biomarker study was to develop serum signatures that could serve as non-invasive indicators of endoscopic improvement and histologic remission after ritlecitinib therapy. Methods: Colon biopsies and peripheral blood were obtained from participants for biomarker profiling before and after receiving 8-week induction therapy with oral ritlecitinib (20mg, 70mg, 200mg, or placebo N=39, 39, 33, 18 respectively) once daily. Responders were defined by endoscopic improvement (Mayo endoscopic sub-score <=1) or histologic remission (Geboes Score ≤ 3.0). RNA from colon biopsy samples were processed using RNA sequencing (Fulgent Therapeutics, CA). Serum proteins were measured using the Olink Explore Inflammation panel (Olink, Proteomics, Sweden). Linear mixed models were used to estimate the change from baseline (CFB) of each protein/gene at Week 8 by treatment and clinical response. Differences between response groups and treatment arms were also analyzed. Results: Analysis of serum revealed 37 proteins significantly changed at week 8 compared to baseline in responders (FDR < 0.05). Changes in four of these proteins (IL4R, TNFRSF4, SPINK4 and LAIR-1) correlate with both endoscopic improvement and histological remission and were able to separate responders from non-responders AUC (area under the ROC curve) = 0.71 [0.61–0.81] based on endoscopic improvement and AUC = 0.60 [0.48–0.71] based on histological remission). To determine if these 37 proteins reflect tissue inflammation, we evaluated the differential expression of genes encoding these proteins with RNA-seq of inflamed biopsies. Ten genes (CXCL1, FCAR, CKAP4, SPINK4, CXCL17, OSM, CD4, CXCL9, IL17A, GZMB) had significant changes from baseline between responders and non-responders at Week 8 (FDR < 0.1) in either endoscopic improvement or histological remission. Furthermore, these ten genes were significantly increased at baseline between inflamed and non-inflamed colon biopsies. Finally, colon biopsy transcription levels of TNFRSF4, SPINK4 and LAIR1 were modulated with marginal significance (P-value < 0.1) in either endoscopic improvement or histological remission at Week 8. Conclusion: Serum proteomics revealed a promising signature of endoscopic improvement and histologic remission in UC participants treated with ritlecitinib. Changes in a subset of these serum proteins parallel tissue gene expression and offer insight into a potential non-invasive companion monitoring test to guide clinical management of patients treated with ritlecitinib.